Application of homotopy perturbation method to the Bratu-type equations - Feng, Xinlong; He, Yinnian; Meng, Jixiang (Topological Methods in Nonlinear Analysis, 2008)
A new algorithm is presented for solving the Bratu-type equations. The numerical scheme based on the homotopy perturbation method is deduced. Two boundary value problems and an initial value problem are given to illustrate effectiveness and convenience of the proposed scheme. Our results agree very well with the numerical solutions showing that the homotopy perturbation method is a promising method.